Practice and Reflection on Renovation of Shanghai Urban Rail Transit Existing Lines - WANG Sitao; WANG Zhenbo; YAO Jianwei (Chengshi guidao jiaotong yanjiu)
[Objective] Shanghai is one of the first batch of cities in China launching urban rail transit systems. In recent years, Shanghai has initiated renovation projects for existing rail lines, undertaking many pioneering explorations and practices. It is necessary to summarize and reflect on the relevant experience to develop methods and approaches for existing line renovation，so as to serve as a reference for future projects. [Method] The background and types of existing line renovation projects in Shanghai are outlined. Practices of existing line renovation without suspending operations and partially suspending operations are introduced. Additionally, the temporal-spatial characteristics of historically implemented partial suspension renovation projects in Shanghai are statistically analyzed. [Result & Conclusion] The non-suspension construction is a fundamental principle for existing line renovation both domestically and internationally. This construction method has advantages in terms of construction duration, quality, and investment, and is particularly suitable for specific scenarios, such as civil engineering renovations involving track areas. Methods such as delayed starts and early closures, retaining trains on the mainline to extend night-time construction windows, and the use of prefabrication, modular design, and process simulation techniques can improve construction efficiency during night-time windows. Measures such as suspending operations during periods of low passenger flow, arranging shuttle buses as alternative transportation, skipping stations under renovation, and establishing mature operational mechanisms can mitigate the impact of partially suspending renovations on passenger travel.